Banks of the World - Orsingher, Roger (New York : Walker, 1967)
Today in all the countries of the world, whether they are capitalist or communist, banks are more than ever essential to the economy, finance, currency, commerce, industry and agriculture.
Translation of Les banques dans le monde.
Includes index
osc 17/7/17
Loans
Keywords: Banks and banking; Banks and Banking, International